Strategic Leadership Approaches To Enhancing Procurement And Supply Chain Optimisation For Operational Excellence - Clottey, Fauzia A. (Journal of International Crisis and Risk Communication Research, 2024)
In the evolving enterprise landscape, procurement and supply chain management have emerged as critical determinants of organizational efficiency and competitiveness. This study examines the role of strategic leadership approaches in enhancing procurement optimisation and supply chain performance to achieve operational excellence. A quantitative research design was employed to assess the influence of leadership dimensions such as vision alignment, decision-making capability, technological adaptability, stakeholder coordination, and governance effectiveness on procurement efficiency and supply chain flexibility. The findings reveal that leadership-driven governance practices significantly improve supplier selection efficiency, sourcing cost effectiveness, and inventory management processes, thereby strengthening operational performance outcomes. Regression and structural modelling analyses indicate that procurement optimisation and supply chain integration mediate the relationship between strategic leadership and enterprise-level operational excellence. Furthermore, technological adaptability emerged as a key leadership attribute influencing procurement responsiveness and supply chain resilience. The study highlights the importance of integrating leadership-driven decision-making frameworks within procurement planning processes to enhance organisational productivity, reduce operational inefficiencies, and ensure sustainable performance in dynamic business environments.